2009
DOI: 10.2106/jbjs.h.00133
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Three and Four-Part Proximal Humeral Fractures

Abstract: In this series, open repair with use of a locked plate resulted in better outcome scores than did hemiarthroplasty in similar patients, especially in those with a three-part fracture, despite a higher overall complication rate. Open reduction and internal fixation of fractures with an initial varus extension pattern should be approached with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
213
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(232 citation statements)
references
References 22 publications
9
213
0
10
Order By: Relevance
“…However, auxiliary exploratory analysis revealed a significant correlation between deviation and the functional result according to the Constant and Murley score: patients with varus deviations greater than 30°to 45°and greater than 45°had, on average, nine (p = 0.008) and 14 (p = 0.027) percentage points less on the relative Constant and Murley score at 1 year, respectively. This finding is consistent with previously reported results from other studies [1,23,28].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, auxiliary exploratory analysis revealed a significant correlation between deviation and the functional result according to the Constant and Murley score: patients with varus deviations greater than 30°to 45°and greater than 45°had, on average, nine (p = 0.008) and 14 (p = 0.027) percentage points less on the relative Constant and Murley score at 1 year, respectively. This finding is consistent with previously reported results from other studies [1,23,28].…”
Section: Discussionsupporting
confidence: 94%
“…One year postoperatively, the mean Constant and Murley score of the injured side for our patients was 72 points corresponding to 87% of the score on the contralateral side. In some other studies, the mean Constant and Murley scores after angular stable plate or angular stable nail fixation of proximal humeral fractures ranged between 72 and 89 points [12,17,21,28,30], which also are comparable to our results. Nevertheless, most of these published studies do not distinguish between different fracture types.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An earlier study from our institution found hemiarthroplasty for acute three-and four-part proximal humerus fractures resulted in effective pain relief but less predictable function and ROM [11]. Dietrich et al [6] and Solberg et al [24] independently observed function is better with locking plate fixation compared to hemiarthroplasty but found no difference in pain reported between the two treatment groups and found a greater incidence of revision surgery/ complications in patients treated operatively.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we examined the early complications of proximal humerus fractures treated with locking plates; 24% of patients had complications and a majority of these were related to intra-articular penetration of screws into the glenohumeral joint [7]. Locking plates reportedly provide comparable ROM, subjective scoring, and pain relief to other forms of fixation and reportedly are associated with better ROM compared to hemiarthroplasty with variable pain relief [2,6,12,24].…”
Section: Introductionmentioning
confidence: 99%